Effects of heavy resistance training on maximal and explosive force production, endurance and serum hormones in adolescent handball players - Gorostiaga, E. M.; Izquierdo, M.; Iturralde, P.; Ruesta, M.; Ibanez, J. (European Journal of Applied Physiology, 1999)
The present findings suggested that the addition of 6-weeks of heavy resistance training to the handball training resulted in gains in maximal strength and throwing velocity but it compromised gains in leg explosive force production and endurance running. The tendency for a compromised testosterone:cortisol ratio observed in the ST group could have been associated with a state of overreaching or overtraining.